The Influence of Digital Technology on Economic Growth in 8 Asean Countries - Berliyani, Diana; Yuliawan, Dedy; Gunarto, Toto (CV. Bimbingan Belajar Assyfa, 2024)
This study explores the impact of individual internet usage, foreign direct investment, and average years of schooling on economic growth in the ASEAN region during the period 2014-2020. The panel regression analysis method was employed to analyze secondary data obtained from the World Bank and UNDP. The results of the fixed-effects regression model indicate that the variables of individual internet usage (IUI) and foreign direct investment (FDI) have a positive and significant impact on economic growth, while the average years of schooling (MYS) do not have a significant impact. These findings are consistent with previous research findings indicating that internet usage and foreign direct investment significantly contribute to economic growth in the region. However, the average years of schooling do not have a significant influence on economic growth in this study's context. The study shows that internet usage and foreign direct investment have a significantly positive impact on economic growth in ASEAN, while the average years of schooling do not have a significant effect. These findings imply that economic development policies in ASEAN should focus on enhancing technology infrastructure and investment environments, as well as reevaluating the education system.